LOAN WORDS IN DIFFERENT LANGUAGES - Mamatova Nilufar Yorkinovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
A loan word is a word borrowed from one language and incorporated into another language. Throughout history, languages have borrowed words from each other for various reasons, such as cultural exchange, trade, or conquest. As a result, many languages have loan words from different languages that have significantly impacted their vocabulary.